THE EFFECT OF FAMILY EDUCATION ON INCREASING KNOWLEDGE AND AWARENESS OF HEALTHY FOOD FOR MOTHERS AND CHILDREN IN PREVENTING STUNTING IN TAHAWA VILLAGE, CENTRAL KAHAYAN DISTRICT: PENGARUH EDUKASI KELUARGA NURANI TERHADAP PENINGKATAN PENGETAHUAN DAN KESADARAN MAKANAN SEHAT IBU DAN ANAK DALAM MENCEGAH STUNTING DI DESA TAHAWA KECAMATAN KAHAYAN TENGAH - Isbaraiati; Saputera; Saiffullah Darlan (SOSIOEDUKASI, 2025)
Stunting is a health problem that has an impact on children's growth and development. Low knowledge and awareness of mothers about healthy food is the main factor that contributes to the high stunting rate. This study aims to analyze the influence of Family Conscience Education on increasing maternal knowledge and awareness in choosing healthy foods to prevent stunting in Tahawa Village, Central Kahayan District. The method used is quasi-experimental with a pretest-posttest design. A total of 55 mothers with children aged 0-5 years became respondents to the study. The results of the Paired Samples Test showed a significant increase in the knowledge aspect with an average score increase of 24.95 points (p < 0.05). The increase in awareness was also significant with the average score increasing by 1.46 points (p < 0.05). These results show that educational interventions are effective in improving maternal understanding of balanced nutrition and healthy diets. Community-based education programs can be a sustainable intervention strategy in stunting prevention.